MY SAY: Keeping pace with bioethics - Abd Razak, Dzulkifli (2010)
Looks like the brave new world has finally arrived. The website BeautifulPeople.com reportedly "booted out 5,000 people who gained weight and were deemed too ugly to remain members". The site, with the tagline "Where beautiful relationships begin", was founded in Denmark in the early 2000s. It was a departure from the notion that "even ugly people" are allowed to subscribe, and to browse for attractive sperm and egg donors.